Preparation method and application of silane-modified high-ortho-phenolic resin

Through the preparation and meltblown process of silane-modified high ortho-position phenolic resin, the existing meltblown nonwoven materials are easily damaged and lacking flame retardant ability in high-temperature environments, and lightweight, high-temperature and flame retardant phenolic meltblown nonwoven materials are achieved, with excellent heat insulation and flame retardant properties and are suitable for personal thermal protection equipment.

CN115947910BActive Publication Date: 2025-03-25TIANJIN YINGWEILUN NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310021361.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-07
Publication Date
2025-03-25
Estimated Expiration
2043-01-07

AI Technical Summary

Technical Problem

Existing meltblown nonwoven materials are prone to damage in high temperature environments and lack flame retardant capabilities, making it difficult to provide sufficient protection in the field of personal thermal protection.

Method used

A silane-modified high ortho-position phenolic resin was designed and synthesized, and lightweight, high temperature-resistant, flame-retardant phenolic melt-blown nonwoven materials were prepared through meltblown process, and the heat insulation and flame-retardant properties of the phenolic resin were used to improve the material's heat insulation and flame-retardant properties.

Benefits of technology

It realizes the soft and fluffy feel of the material, excellent flame retardant and heat insulation performance, can effectively protect the human body from damage from flames and high-temperature objects, and has huge application potential in the field of personal thermal protection equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115947910B_ABST
    Figure CN115947910B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a silane-modified high-ortho-phenolic resin, and relates to the technical field of melt-blown nonwoven materials. The preparation method of the silane-modified high-ortho-phenolic resin comprises the following steps: synthesizing a high-ortho-phenolic resin intermediate under the ortho-induction of a divalent metal salt catalyst; modifying and extending the methylene bond rigid chain of the phenolic resin by introducing a siloxane flexible chain through a silane modifier to obtain a silane-modified high-ortho-phenolic resin; conducting a fiber-forming process and performance study on the silane-modified high-ortho-phenolic resin through melt spinning, successfully preparing a silane-modified high-ortho-phenolic fiber, and being able to spin at high speed to produce a continuous soft long fiber with a thin diameter, high strength and softness; preparing a phenolic melt-blown nonwoven material composed of ultrafine fibers using the silane-modified high-ortho-phenolic resin as a raw material through a melt-blowing process, and obtaining excellent thermal insulation performance due to its high porosity and small pore size structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of melt-blown nonwoven materials, and in particular relates to a preparation method and application of a silane-modified high-ortho-phenolic resin. Background Art

[0002] In recent years, casualties have occurred in various fires, explosions, high-temperature furnaces and other high-temperature harsh environments. Thermal damage caused by high-temperature environments is one of the important factors leading to casualties. Therefore, flame-retardant, high-temperature resistant, and heat-insulating thermal protective textiles are increasingly receiving attention and concern.

[0003] In the past few decades, advanced thermal insulation materials such as aerogels, polymer foams and glass fibers have developed rapidly, but their applications in the field of personal thermal protection equipment are limited due to their poor softness, poor comfort and unsuitability for wear. In contrast, existing high-performance thermal protection fabrics such as electrospun fiber felt can meet the various needs of personal thermal protection equipment, but due to their low production efficiency and complex processes, they cannot be mass-produced and are still not widely used in personal thermal protection equipment.

[0004] Meltblowing is an industrial technology that directly converts polymer resin into nonwoven materials with submicron diameter fibers. This method has significant advantages such as simplicity, high output and solvent-free operation. More importantly, meltblown nonwoven fabrics have the characteristics of high porosity (≥85%) and small pore size (pore size ≤20μm), which are very suitable for use in the field of thermal insulation. For example, polypropylene meltblown nonwoven materials are widely used in the field of thermal insulation. So far, some thermoplastic polymers (such as polypropylene, polylactic acid, polyester) have been widely used as meltblown raw materials. However, their low melting point characteristics cannot withstand high temperature environments. When the use environment exceeds the melting point of the polymer, the fabric structure will be destroyed and lose its function. Especially in the field of personal thermal protection, it is possible that molten droplets will cause additional damage to the human body due to heating. In addition, the existing meltblown nonwoven materials themselves do not have flame retardant ability, and often require fabric flame retardant finishing. The flame retardant effect of the flame retardant finishing agent is limited and the combustion is often accompanied by harmful gases. This also makes the role of meltblown nonwoven materials in the field of personal thermal protection limited, and it is difficult to provide sufficient and effective protection for the human body in extremely harsh environments. Therefore, the ability to produce meltblown nonwoven materials with flame retardancy and high temperature resistance is an urgent need in the field of thermal protection.

[0005] The molecular structure of phenolic resin is a three-dimensional network structure with two benzene rings connected by methylene bonds. The bond energy of the molecular structure is large, and the mutual cohesion between the molecular chains is high but the rigidity is large, which leads to the prepared phenolic fiber having excellent flame retardant and high temperature resistance, but strong brittleness and poor flexibility. With the continuous expansion of the application field of phenolic fiber and the continuous improvement of the requirements for product performance, the phenolic fiber is modified to improve its flexibility and pursue better flame retardant and high temperature resistance.

[0006] Although there are many existing methods for chemical synthesis and modification of phenolic fibers, and the performance of the modified phenolic fibers prepared is significantly improved compared to that of unmodified phenolic fibers, there is still much room for improvement in the spinnability of phenolic fibers. The problem that phenolic fibers are prone to breakage during the production process and the primary fibers are difficult to unwind are still urgent issues to be solved in the industrial production of phenolic fibers.

[0007] In view of the above problems, the present invention designs and synthesizes a silane-modified high-ortho-phenolic resin, and prepares it into a lightweight, high-temperature-resistant, flame-retardant phenolic melt-blown nonwoven material that can be applied to the field of personal thermal protection through a melt-blown process. The phenolic melt-blown nonwoven material (SiPR-MBNM) has a soft and fluffy feel and excellent flame-retardant and heat-insulating properties due to its high porosity, small pore size structural characteristics and the inherent flame-retardant properties of the phenolic resin after post-crosslinking treatment. In addition, SiPR-MBNM is used as a heat-insulating layer to make thermal protective clothing, and its application performance is characterized. The thermal protective clothing can protect the human body from flames and high-temperature objects during actual use due to its excellent heat-insulating properties, which fully proves that SiPR-MBNM has great application potential in the field of personal thermal protection equipment. Summary of the invention

[0008] To achieve the above object, the present invention adopts the following technical solutions:

[0009] A method for preparing a silane-modified high-ortho-phenolic resin comprises the following steps:

[0010] S1. Synthesizing a high-ortho-phenolic resin intermediate by ortho-induction of a divalent metal salt catalyst;

[0011] S2. A silane-modified high-ortho-phenolic resin (SiPR) is obtained by introducing a siloxane flexible chain through a silane modifier to modify and extend the methylene bond rigid chain of the phenolic resin.

[0012] Preferably, the synthesis of the high-ortho-phenolic resin intermediate in S1 comprises the following steps:

[0013] S11, mixing phenol, formaldehyde and zinc acetate, placing them in a reactor equipped with a condenser reflux tube, a mechanical stirrer and a thermometer, and reacting them under heating conditions;

[0014] S12, the first stage pre-reaction needs to continue to react at 75-85°C for 3-5 hours;

[0015] S13, then adding hydrochloric acid catalyst to adjust the pH value to 1.5-2.5, heating the mixture to reflux temperature and continuing the reaction for 1-3 hours to obtain a phenolic resin reaction intermediate.

[0016] Preferably, in S11, phenol, formaldehyde and zinc acetate are mixed in a molar ratio of 1:0.5-0.95:0.01-0.05.

[0017] Preferably, obtaining the silane-modified high-ortho-phenolic resin in S2 comprises the following steps:

[0018] S21, adding dimethyldimethoxysilane (DDS) as a modifier, and continuing the reaction for 2-8 hours to obtain a mixture containing a silane-modified high-ortho-phenolic resin;

[0019] S22, dissolving the mixture in anhydrous ethanol and removing excess water, unreacted phenol and other impurities by vacuum distillation;

[0020] S23, finally drying in a vacuum oven at 100-150°C for 12-36 hours.

[0021] Preferably, the mass ratio of phenol in the dimethyldimethoxysilane modifier is set to 3% to 11%.

[0022] Preferably, the DDS modifier is set to 3%, 5%, 7%, 9% and 11% DDS modifier according to the mass ratio of phenol, and the SiPRs obtained according to the DDS content are SiPR-3, SiPR-5, SiPR-7, SiPR-9 and SiPR-11 respectively.

[0023] A method for preparing silane-modified high-ortho-phenolic resin fiber is provided, and the silane-modified high-ortho-phenolic resin fiber is prepared by using the preparation method as a raw material.

[0024] Preferably, the preparation method comprises the following steps:

[0025] A1. Before melt spinning, place the silane-modified high-ortho-phenolic resin in a vacuum oven at 80-120°C and dry for 2-8 hours;

[0026] A2, spinning is completed by a melt spinning machine at a spinning temperature of 100-110° C. and a spinning speed of 40-150 r / min;

[0027] A3, soaking the melt-spun fiber in a cross-linking bath containing 10-25% hydrochloric acid and 10-25% formaldehyde for curing, heating from 25°C to boiling point at a heating rate of 5-35°C / h and maintaining heating for 1-3 hours;

[0028] A4. The cured fiber is washed with deionized water for two to three times, and heat treated at 120-250° C. for 1-3 hours to obtain silane-modified high-ortho-phenolic fiber (SiPRF).

[0029] Preferably, the SiPRF is melt-spun using SiPR with different DDS contents as raw materials, and the obtained SiPRFs are named SiPRF-3, SiPRF-5, SiPRF-7, SiPRF-9 and SiPRF-11 respectively.

[0030] A method for preparing a silane-modified high-ortho-phenolic melt-blown nonwoven material adopts the silane-modified high-ortho-phenolic resin prepared by the preparation method as a raw material for preparation.

[0031] Preferably, the preparation method comprises the following steps:

[0032] B1. Dry the silane-modified high-ortho-phenolic resin in a vacuum oven at 80-120°C for 2-8 hours;

[0033] B2. Prepare melt-blown nonwoven material by melt-blown machine, and the processing temperature of melt-blown and hot air drawing temperature are controlled at 100-150°C;

[0034] B3, the obtained melt-blown nonwoven material is immersed in a cross-linking bath containing 10-25% hydrochloric acid and 10-25% formaldehyde for curing, and heated from 25°C to boiling point at a heating rate of 5-35°C / h and kept heated for 2 hours;

[0035] B4. The cured fibers were washed with deionized water for two to three times, and heat treated at 120-250° C. for 1-3 hours to obtain a phenolic melt-blown nonwoven material (SiPR-MBNM).

[0036] Beneficial Effects

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] (1) The present invention designs and synthesizes a silane-modified high-ortho-phenolic resin. First, the design is to solve the brittleness problem caused by the inherent rigid chain of PF by introducing additional flexible chains to improve flexibility, that is, adding a silane modifier to introduce -Si-O-flexible chains during the synthesis of phenolic resin, and the toughness of phenolic resin is enhanced by extending the flexible chains to the inherent methylene bond rigid chains. In addition, a dimethyl metal ion medium catalyst is added during the synthesis process, and the ortho-para ratio (O / P) of the phenolic resin is increased through the ortho-directing effect induced by a divalent metal salt, thereby obtaining a phenolic resin with a narrower molecular weight distribution and a higher molecular weight, thereby achieving the purpose of improving its melt processing performance.

[0039] (2) The present invention studies the fiber-forming process and performance of silane-modified high-ortho-phenolic resin by melt spinning, successfully prepares silane-modified high-ortho-phenolic fiber, and verifies that silane-modified high-ortho-phenolic resin has better spinnability than unmodified PF, and can be spun at high speed to produce continuous soft long fibers with fine diameter, high strength and softness, among which SiPRF-7 exhibits excellent mechanical properties (tensile breaking strength: 245.5MPa, tensile breaking elongation: 6.63%) and good heat resistance (residual carbon rate: 61%). Subsequently, a phenolic melt-blown nonwoven material composed of melt-blown ultrafine fibers was prepared using SiPR-7 as raw material through a melt-blowing process. Due to its high porosity and small pore size structure, it has excellent thermal insulation performance, and the thermal conductivity is only 0.03-0.037W·m -1 ·K -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a design diagram of the SiPR synthesis and cross-linking curing molecular formula in Example 1;

[0041] Figure 2 is the infrared spectrum of SiPR and PF in Example 1;

[0042] Figure 3 is the full XPS scanning spectrum of SiPR-7 and PF in Example 1;

[0043] Figure 4 is the O1s peak spectrum of SiPR-7 in Example 1;

[0044] Figure 5 is the Si 2p peak spectrum of SiPR-7 in Example 1;

[0045] Figure 6 is the NMR spectrum of SiPR-7 in Example 1;

[0046] Figure 7 yes Figure 6 Detailed display of area "b";

[0047] Figure 8 is a diagram of three methylene bonding modes between phenolic hydroxyl groups of phenolic resin in Example 1;

[0048] Fig. 9 is a comparison chart of the molecular weights of SiPR with different DDS addition ratios in Example 1;

[0049] Fig.10 is a DSC test comparison diagram of SiPR with different DDS addition ratios in Example 1;

[0050] Fig.11 Comparison of rheological curves of SiPR with different DDS addition ratios at different temperatures in Example 1 Figure 1 ;

[0051] Fig.12 Comparison of rheological curves of SiPR with different DDS addition ratios at different temperatures in Example 1 Figure 2 ;

[0052] Fig.13 Comparison of rheological curves of SiPR with different DDS addition ratios at different temperatures in Example 1 Figure 3 ;

[0053] Fig.14 is a graph showing the change in SiPR viscosity with the addition ratio of DDS at different temperatures under a constant shear rate in Example 1;

[0054] Fig.15 is a flow chart for preparing SiPR-MBNM in Example 3;

[0055] Fig.16 are the surface and cross-sectional electron micrographs of the PPF and SiPRF in Example 2;

[0056] Fig.17 is a diagram showing the spun fibers and cured fibers of SiPRF in Example 2;

[0057] Fig.18 is a comparison chart of the tensile breaking strength and tensile breaking elongation of SiPRF with different DDS addition ratios in Example 2;

[0058] Fig.19 is a comparison diagram of Tg curves of SiPRF with different DDS addition ratios in Example 2;

[0059] Fig. 20 is a physical display diagram of SiPR-MBNM in Example 3;

[0060] Fig.21 It is the electron microscope image of SiPR-MBNM and melt-blown fiber in Example 3;

[0061] Fig. 22 is an infrared thermal imaging image of the thermal insulation performance of SiPR-MBNM with different thicknesses in Example 3;

[0062] Fig.23 is a heated side-view thermal infrared thermal image of SiPR-MBNM-4mm in Example 3;

[0063] Fig.24 (a) The heating curves of SiPR-MBNM-2mm and SiPR-MBNM-4mm and the temperature difference curve with the heating plate; (b) The heating and cooling cycle curves of SiPR-MBNM-2mm;

[0064] Fig.25 is a comparison diagram of heat release rate curves of SiPR-MBNM and commercial thermal insulation materials in Example 3;

[0065] Fig.26 is a comparison chart of the flame retardant properties of SiPR-MBNM and commercial thermal insulation materials in Example 3;

[0066] Fig. 27 (a) STPG thermal insulation test demonstration diagram, (b) STPG internal temperature variation curve with combustion time, (c) infrared thermal imaging demonstration diagram of STPG thermal insulation performance. DETAILED DESCRIPTION

[0067] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0068] Example 1: Preparation of silane-modified high-ortho-phenolic resin

[0069] Considering that the main chain connection of phenolic resin itself mainly relies on the relatively fragile and rigid methylene bond connection, this is the main reason why phenolic resin is difficult to form fibers and easy to break during the spinning process. Therefore, the brittleness and processing problems of phenolic resin need to be improved at the molecular level. In order to obtain PF with good toughness and spinnability, the following two problems must be considered: (i) the brittleness problem caused by the inherent rigid chain of PF, and (ii) the poor melt processing performance caused by low molecular weight and irregular chains.

[0070] In view of the above problems, the present invention first designs to solve the brittleness problem caused by the inherent rigid chain of PF by introducing additional flexible chains to improve flexibility, that is, adding a silane modifier to introduce -Si-O-flexible chains during the synthesis of phenolic resin, and the phenolic resin enhances toughness by extending the flexible chains to the inherent methylene bond rigid chains. In order to meet the second requirement, a dimethyl metal ion medium catalyst is added during the synthesis process, and the ortho-para ratio (O / P) of the phenolic resin is increased through the ortho-directing effect induced by a divalent metal salt, so as to obtain a phenolic resin with a narrower molecular weight distribution and a higher molecular weight, thereby achieving the purpose of improving its melt processing performance.

[0071] See also Figure 1 , which is the chemical synthesis molecular formula design of SiPR. First, the carbonyl group of formaldehyde will be protonated in an acidic environment, and then the protonated carbonyl group will attack the ortho and para carbon atoms of phenol to undergo electrophilic aromatic substitution reactions to form hydroxymethylphenol intermediates, and under the influence of the metal medium catalyst, the reaction will mainly occur at the ortho position. Subsequently, the condensation reaction between hydroxymethylphenols and the reaction of hydroxymethylphenol with dimethyldimethoxysilane (DDS) modifier are carried out simultaneously. In the case of excessive phenol, a high ortho linear phenolic resin containing a flexible silane chain will be formed. At this time, SiPR has a linear structure with thermoplastic processing properties, and can meet various requirements through melt processing. It can then be further cured into a three-dimensional cross-linked network structure by a cross-linking bath or by adding a curing agent, thereby obtaining an infusible phenolic resin. The SiPR synthesized by this molecular formula design can theoretically obtain better melt processing properties and better toughness.

[0072] (1) Preparation of SiPR using a one-step synthesis method

[0073] Phenol, formaldehyde and zinc acetate were mixed in a molar ratio of 1:0.85:0.03 in a three-necked flask equipped with a condenser reflux tube, a mechanical stirrer and a thermometer, and the mixture was heated in an oil bath for reaction. The first stage of the pre-reaction was to continue the reaction at 85°C for 3 hours; then an appropriate amount of hydrochloric acid catalyst was added to adjust the pH value to 1.5-2.5, and the mixture was heated to reflux temperature for 1 hour, at which time a phenolic resin reaction intermediate was obtained; 3%, 5%, 7%, 9% and 11% DDS modifier (mass ratio of phenol) was added, and the reaction was continued for 5 hours to obtain a mixture containing SiPR; the mixture was dissolved in anhydrous ethanol and the excess water and unreacted phenol and other impurities were removed by vacuum distillation; finally, it was dried in a vacuum oven at 120°C for 24 hours. According to the content of DDS, the obtained SiPRs were named SiPR-3, SiPR-5, SiPR-7, SiPR-9 and SiPR-11.

[0074] (2) SiPR performance testing and characterization

[0075] Conduct Fourier transform infrared spectroscopy (FT-IR) testing and characterization, X-ray photoelectron spectroscopy (XPS) testing and characterization, liquid nuclear magnetic resonance spectroscopy (NMR) testing and characterization, gel permeation chromatography (GPC) testing and characterization, differential scanning calorimetry (DSC) testing and characterization, and rheological properties testing and characterization.

[0076] (3) Verification of the molecular formula structure of silane-modified high-ortho-phenolic resin

[0077] In order to verify whether the above molecular formula design can successfully synthesize SiPR through experiments, the present invention uses a variety of chemical structure basic tests to characterize the molecular formula structure of SiPR synthesized according to the design scheme. SiPR-7 is used as a verification sample, and unmodified PF is used as an experimental control for various tests. The PF synthesis method is consistent with the SiPR conditions except for the modified part.

[0078] Firstly, infrared testing was used to analyze the changes in the chemical structure of the resin before and after modification. Figure 2 This is the FTIR test spectrum of SiPR-7 and unmodified PF. It can be clearly seen that the SiPR-7 and PF curves are at 3340 cm -1 The hydroxyl (-OH) vibration peak at 1593cm -1 The vibration peak of the benzene ring double bond (C=C) at 1441cm -1 and 1472cm -1 The deformation vibration peak of methylene (-CH2-) at 750cm -1 and 811cm -1 The absorption peaks at 1102cm and 1102cm are the absorption peaks of benzene ring ortho-substitution and benzene ring para-substitution, which are the characteristic peaks of phenolic resin. It also indirectly shows that the modified SiPR still maintains the characteristics of phenolic resin and does not have a serious chemical structure deviation due to excessive modification. It is worth noting that the SiPR-7 curve at 1102cm -1 and 1008cm -1 New absorption peaks appeared at these two absorption peaks, which are stretching vibration peaks caused by -Si-OC-, indicating that the silicon-oxygen bonds in DDS reacted with the phenolic resin intermediate hydroxymethylphenol, and successfully participated in the synthesis modification to introduce the siloxane flexible chain into the molecular structure of the phenolic resin. In addition, the benzene ring ortho-substitution and para-substitution absorption peaks of the SiPR curve have obvious changes compared with the PF curve. The benzene ring ortho-substitution absorption peak of SiPR is significantly higher than the para-substitution absorption peak, which directly indicates that the high ortho-substitution of SiPR is successful. Therefore, the resin synthesized by this scheme can be qualitatively characterized, and SiPR can be successfully synthesized.

[0079] See also Figure 3-5XPS is an important means of qualitative and quantitative characterization of chemical structure. XPS test is used to characterize it and further verify whether DDS is involved in chemical synthesis. From the overall analysis, Figure 3 The full XPS scan spectrum of SiPR-7 and PF shows that the SiPR-7 curve has three significant characteristic peaks, O1s, C 1s, and Si 2p, while PF has only two characteristic peaks, O1s and C 1s. At the same time, from the peak intensity comparison, it is found that the O1s characteristic peak of SiPR-7 is significantly higher than that of PF. Both phenomena indicate the successful introduction of -Si-O-. The SiPR-7 curve is further analyzed by peak separation and fitting. Figure 4 This is the peak fitting analysis diagram of SiPR-7 at the O1s peak. After peak fitting, SiPR-7 fits characteristic peaks at 532.9eV, 532.5eV and 531.8eV, which correspond to the characteristic peaks of OC, O-Si and OH respectively. Figure 5 This is the peak fitting analysis diagram of SiPR-7 at the Si 2p peak. After fitting, the Si peaks at 102.4eV and 101.8eV are attributed to the characteristic peaks of Si-O and Si-C respectively. From the above analysis, it can be concluded that in the XPS spectrum of SiPR-7, the characteristic peak of Si-O can be fitted from the O1s peak and the Si 2p peak, while PF cannot find silicon in the full spectrum scan. Combined with the infrared test results in the previous article, it fully illustrates that DDS participated in the reaction during the synthesis of SiPR-7, allowing the -Si-O- flexible chain to successfully extend PF.

[0080] In order to determine the molecular formula of SiPR-7 and verify whether it is consistent with the designed molecular formula, and quantitatively calculate its ortho-para ratio (O / P) value, 13 C NMR test was performed to analyze SiPR-7. Figure 6 As shown, the chemical shift of the solvent deuterated methanol used is around 49 ppm, which is not analyzed. First, region "a" is the chemical shift of the benzene ring in SiPR-7, which is distributed between 115-156 ppm; Figure 7 The detailed diagram of region "b" is a chemical shift of the methylene bond (-CH2-) connecting two phenolic hydroxyl groups in the SiPR molecular chain skeleton. There are three ways to connect two phenolic hydroxyl groups, such as Figure 8As shown are: ortho-ortho (o-o'), ortho-para (o-p') and para-para (p-p'), the chemical shifts are distributed around 31, 35.5 and 41 ppm respectively; area "c" is the chemical shift of -CH3 and -CO- in the silanes involved in the reaction in SiPR-7, which are distributed between 58-60 ppm and -10-0 ppm respectively. From the above analysis of the NMR spectrum, it can be clearly seen that the synthesized SiPR-7 is roughly consistent with the molecular formula designed by the present invention, which better proves the feasibility of the molecular formula design scheme. In addition, by integrating the characteristic peaks of the NMR spectrum of SiPR-7 and calculating according to formula (1), the O / P of SiPR-7 can be obtained.

[0081] value:

[0082] Ao-o', Ao-p' and Ap-p' are the integral values ​​of the characteristic peak intensities corresponding to o-o', o-p' and p-p' in NMR test. The O / P of SiPR-7 is calculated by the formula to be 3.73 (Ao-o': 2.57, Ao-p': 1.58, Ap-p': 0.11), which is much higher than the O / P value of unmodified PF (0.5-1.2).

[0083] Through the characterization and analysis of the above tests, the feasibility of synthesizing SiPR by DDS modification and high ortho-modification has been fully confirmed, and the synthesized SiPR is consistent with the designed molecular structure. SiPR modified by high ortho-modification of silane can improve its toughness by introducing -Si-O- flexible chain, and the higher O / P enables SiPR-7 to obtain a narrower molecular weight distribution. At the same time, the regularity of the molecular chain is also improved with the reduction of methylene bonds at p-p', which theoretically enables it to obtain better melt processing performance.

[0084] (4) Effect of different DDS modifier addition ratios on SiPR melt processing performance

[0085] In order to explore the effect of the addition ratio of DDS modifier on the melt processing performance of SiPR and select the optimal melt processing conditions and parameters of SiPR, the present invention conducted various tests and characterizations on SiPR with different modification ratios (SiPR-3, SiPR-5, SiPR-7, SiPR-9 and SiPR-11) and unmodified PF.

[0086] Fig. 9The figure shows the comparison of the number average molecular weight (Mn) and weight average molecular weight (Mw) of SiPR with different amounts of DDS modifier added. Molecular weight is an important parameter to characterize the melt processing performance of polymers. Too small molecular weight and wide molecular weight distribution (molecular weight distribution index: D = Mw / Mn) will lead to difficulties in molding during processing, especially the rigid chain structure of PF itself is very easy to break after melt processing and cooling, which is more likely to cause the fiber to be unable to be continuously produced or even unable to be molded. It can be clearly seen from the figure that under the same synthesis conditions, the Mn and Mw of the modified SiPR are significantly improved, and the increase in molecular weight increases with the addition of DDS modifier, especially Mn has a huge improvement. The Mn of SiPR-11 is doubled compared to PF, which shows that the chain extension modification of DDS modifier has played a role. At the same time, it can be clearly seen from the figure that the molecular weight distribution index of SiPR (1.23-1.31) is much smaller than that of PF (1.79). This is because the high ortho-modification also greatly improves the uniformity of the molecular chain of SiPR, making it easier for the resin to form longer and more regular molecular chains during the synthesis process, and also promotes the synthesis of SiPR to obtain a narrower molecular weight distribution, which is more conducive to melt processing and molding.

[0087] See also Fig.10 Differential scanning calorimetry (DSC) testing is an important means to characterize the thermal properties of polymerization. By performing DSC testing on SiPR and PF, we can better analyze their processing performance and state during thermal processing. Fig.10 The DSC curves of SiPR with different DDS modifier additions are compared. It can be seen from the figure that even after modification, SiPR still presents the same standard curve of thermoplastic resin as PF, and as the amount of DDS modifier added increases, the glass transition temperature (Tg) of SiPR also increases. This trend is consistent with Fig. 9 The change trend of the molecular weight is consistent. This is because molecular weight is an important factor affecting Tg. A larger molecular weight will reduce the free volume and segment freedom of the polymer, limit the segment activity, and thus lead to an increase in Tg.

[0088] See also Figure 11-13 ; Rheology plays an important role in studying the flow and deformation ability of polymers during processing. In order to characterize the effect of modifier addition on the melt processing properties of SiPR and select the optimal melt processing temperature of SiPR, the rheological properties of SiPR with different DDS contents at 100℃, 105℃, and 110℃ were tested with PF as a control. Figure 11-13As shown, all resins exhibit typical non-Newtonian fluid properties, and the viscosity decreases with increasing shear rate. This is because with increasing shear rate, the increase in the disentanglement rate of macromolecules is greater than the increase in entanglement speed. At the same time, the free volume and degree of freedom of the chain segment increase with increasing temperature, which causes the viscosity of the polymer to decrease with increasing temperature, that is, the "shear thinning" phenomenon. Among them, the initial viscosity of the resin at 100°C is relatively high (30-90Pa.S). With increasing temperature, the initial viscosity gradually decreases, and at 110°C, the initial viscosity decreases rapidly (5.4-14Pa.S), indicating that in this temperature range, the entanglement speed and disentanglement speed of macromolecules are in a stage of rapid change, which can better analyze the effect of temperature on the melt processing performance of SiPR.

[0089] From the figure, it can be seen that the viscosity of the modified SiPR is higher than that of the unmodified PF, and the viscosity is positively correlated with the amount of DDS added. In addition, when the shear rate exceeds 100s -1 After that, all resins will gradually experience severe shear thinning at different temperatures, and the sharp drop in viscosity is not conducive to the molding process of polymer melts. Therefore, the processing shear rate of SiPR should be controlled before severe shear thinning occurs, that is, the shear rate should be less than 100s -1 At the same time, it can be clearly seen from the figure that the viscosity span of SiPR with more DDS modifier is larger. This is because with the addition of DDS modifier, the molecular weight of SiPR continues to increase, resulting in a higher initial viscosity, but its siloxane flexible chain content also increases, which also leads to a stronger disentanglement ability. This also leads to SiPR with too high DDS modifier addition, such as SiPR-9 and SiPR-11, not being suitable for melt processing.

[0090] Fig.14 The figure shows the change trend of resin with different DDS addition at different temperatures at the same shear rate. The figure shows that at 105℃ and 110℃, with the increase of DDS modifier content, the viscosity of the resin does not change significantly, showing a slight upward trend, which means that when the temperature exceeds 105℃, the resin has been fully melted to a state that can be thermoplastic processed. On the contrary, the viscosity of the resin will increase significantly at 100℃ with the increase of modifier addition. This is due to the different Tg of the resin ( Fig.10 ), the previous analysis shows that Tg increases with the increase of modifier content, which causes the molecular chains of resins with high modifier content to remain entangled at 100°C and still maintain a high viscosity. At this time, resins with high modifier content are not suitable for thermoplastic processing at this temperature.

[0091] In view of the problems of PF's own brittle rigid chain and poor melt processing performance due to low molecular weight and irregular chain segments, the present invention designs and synthesizes silicon-modified high-ortho-phenolic resin, and tests its structure and performance. The main conclusions are as follows:

[0092] 1) The molecular structure of SiPR-7 was characterized by FTIR, XPS and NMR tests, verifying the feasibility of the silane high-ortho modification scheme. The synthesized SiPR-7 successfully introduced the siloxane flexible chain, and the molecular formula of SiPR-7 was basically consistent with the molecular formula structure in the design scheme. SiPR was finally obtained by combining DDS and hydroxymethylphenol through a condensation reaction;

[0093] 2) The O / P values ​​of SiPR-7 and PF were calculated by NMR spectrum. The O / P of SiPR-7 was calculated to be 3.73 by the formula, which was much higher than the O / P value of unmodified PF (0.5-1.2), indicating that the high ortho-position modification of SiPR was successful;

[0094] 3) Through gel chromatography test of SiPR, it is known that the Mn and Mw of SiPR increase with the increase of the addition amount of DDS modifier, and the molecular weight distribution index is only 1.23-1.31, which is greatly improved compared with the unmodified PF (1.79). This shows that the silane high ortho-modification synthesis scheme enables SiPR to obtain a longer and more regular molecular chain and a significant improvement in molecular weight uniformity, which promotes the synthesis of SiPR to obtain a narrower molecular weight distribution, which is more conducive to melt processing and molding;

[0095] 4) The rheological properties of SiPR were tested and it was found that the viscosity of SiPR decreased with the increase of shear rate at different temperatures, and the most suitable SiPR for melt processing were analyzed through the rheological curves of SiPR with different DDS modifier addition amounts: SiPR-3, SiPR-5, and SiPR-7. At the same time, the viscosity performance of the resin at different temperatures was analyzed and the temperature range for melt processing of SiPR was more suitable: 105-110℃.

[0096] Example 2: Preparation of silane-modified high-ortho-phenolic fiber;

[0097] (1) Preparation method of silane-modified high-ortho-phenolic fiber

[0098] SiPRF was melt-spun with SiPR with different DDS contents as raw materials. Before melt spinning, SiPR was placed in a vacuum oven at 80°C and dried for 5 hours. The spinning was completed by a laboratory-made melt spinning machine at a spinning temperature of 100-110°C and a spinning speed of 120r / min. The melt-spun fibers were immersed in a cross-linking bath containing 18% hydrochloric acid and 18.5% formaldehyde for curing, heated from 25°C to boiling point at a heating rate of 15°C / h and kept heated for 2 hours. Finally, the cured fibers were washed two to three times with deionized water and heat-treated at 165°C for 2 hours to obtain SiPRF. According to the content of DDS, the obtained SiPRFs were named SiPRF-3, SiPRF-5, SiPRF-7, SiPRF-9 and SiPRF-11, and the fibers spun from unmodified PF were named PFF.

[0099] (2) Performance test and characterization of silane-modified high-ortho-phenolic fiber

[0100] Scanning electron microscopy (SEM), tensile properties testing, thermogravimetric analysis (TG), thermal conductivity testing and characterization, thermal infrared testing and characterization, microcalorimetry (MCC) testing and characterization, and limiting oxygen index (LOI) testing and characterization were performed.

[0101] (3) Test results

[0102] Surface morphology characterization of silane-modified high-ortho-phenolic fiber

[0103] Fig.16 The surface and cross-sectional morphology of PFF and SiPRF. It can be clearly seen from the figure that the diameter of PFF is much larger than that of SiPRF. This is because PF itself is very easy to break during the spinning process due to its own brittleness, and it is impossible to spin long fibers with lower diameters at a higher drawing rate. SiPR has better flexibility due to silane chain extension and high ortho-position modification, and can spin ultrafine fibers with a diameter of only 4μm at a higher spinning speed. In addition, the tensile fracture cross-sectional diagrams of PFF and SiPRF show that ( Fig.17 (b), (d), the fiber fracture section of PFF is flat and has no obvious deformation, which is a typical brittle fracture section. The fracture section of SiPRF is a tearing and pulling fracture morphology, which is a typical tough tensile fracture section), which indirectly proves that the toughness of SiPRF is greatly improved compared with PFF.

[0104] Fig.17 (a) is a diagram showing the flexibility of the nascent SiPRF. It can be observed that SiPRF can be easily bent, rotated and wound. The nascent fiber with such excellent flexibility can be easily unwound for subsequent crosslinking processes. Further crosslinking and curing in a H+, CH2OH+ environment crosslinking bath can obtain infusible SiPRF ( Figure 1 ).like Fig.16 As shown in (b), the SiPRF after curing is golden yellow in color. Since SiPRF forms a three-dimensional cross-linked structure after cross-linking, the fiber strength is further improved compared to the nascent SiPRF, and single fiber knotting can be easily achieved without breaking.

[0105] The flexibility and fiber strength of SiPRF and PFF were further characterized by tensile properties testing. Fig.18 This is a test chart of the tensile properties of PFF and SiPRF with different DDS contents. The figure shows that the tensile breaking strength of the fiber increases with the increase of the DDS addition ratio, and can reach a maximum of 318.2MPa, which is 137.3% higher than the 134.3MPa of the unmodified PF. The tensile breaking elongation shows a trend of first increasing and then decreasing with the increase of the DDS addition ratio. The maximum breaking elongation appears in SiPRF-7, which is 6.63%, and the minimum breaking elongation is SiPRF-11, which is only 2.3%. The main reason for this phenomenon is that after SiPR is modified by DDS chain extension, the original fragile methylene bond of PF is replaced by a stronger siloxane chain, so the tensile breaking strength is significantly improved; similarly, when the fiber strength increases to a certain extent with the increase of DDS content, the fiber rigidity also increases, resulting in a decrease in fiber toughness and a decrease in tensile breaking elongation.

[0106] The residual carbon rate is one of the important indicators to characterize the performance of phenolic fiber. Fig.19 The thermogravimetric test curve of SiPRF and PFF. It can be clearly seen from the figure that the residual carbon rate of SiPRF is higher than that of PFF, and the overall trend is that it increases with the increase of DDS addition, and can reach up to 66.3%; the temperature of resin weight loss of 20% increased from less than 400℃ to a maximum of 500℃, and the temperature of weight loss of 30% increased from 450℃ to a maximum of 660℃, and the heat resistance was significantly enhanced. This may be due to the synergistic effect of DDS chain extension and high ortho-modification, which makes the three-dimensional cross-linking degree of SiPR higher, and at the same time, the Si-O bond energy in SiPR is greater than the CO bond, thereby alleviating the oxidation process of phenolic hydroxyl groups at high temperatures.

[0107] In summary, SiPRF has improved both mechanical properties and heat resistance compared to PFF, among which SiPRF-7 shows excellent mechanical properties and good heat resistance. From the test results, SiPRF-7 has the most outstanding tensile performance, with a high tensile breaking strength (245.5MPa) and the best tensile breaking elongation (6.63%). In addition, SiPRF-7's thermogravimetric performance is also much better than PFF, reaching 61%.

[0108] Example 3: Preparation of silane-modified high-ortho-phenolic melt-blown nonwoven material;

[0109] (1) Preparation method of silane-modified high-ortho-phenolic melt-blown nonwoven material

[0110] The preparation process of SiPR-MBNM is as follows Fig.15 As shown, SiPR-7 was used as raw material to prepare melt-blown nonwoven materials through a laboratory-made melt-blown machine. SiPR-7 was placed in a vacuum oven at 80°C for 5 hours before the melt-blowing process. The processing temperature of melt-blowing and the hot air drawing temperature were both controlled at 100-150°C. The obtained melt-blown nonwoven material was subjected to the same cross-linking process as SiPRF to obtain SiPR-MBNM.

[0111] (2) Performance testing and characterization of silane-modified high-ortho-phenolic melt-blown nonwoven materials

[0112] The silane-modified high-ortho-phenolic meltblown nonwoven material was subjected to the same performance tests as the silane-modified high-ortho-phenolic fiber.

[0113] (3) Test results

[0114] Thanks to the excellent performance of SiPRF-7 in tensile and heat resistance tests, SiPR-7 was used as raw material to prepare SiPR meltblown nonwoven fabric (SiPR-MBNM) through meltblowing process. Fig. 20 This is a physical display picture of SiPR-MBNM. It can be clearly seen from the picture that SiPR-MBNM is soft and fluffy, and can be easily bent and folded to meet various flexibility requirements. The fluffy melt-blown microfiber can be clearly seen on the surface of SiPR-MBNM, which feels soft and can be bent into any shape, which well ensures the wearing comfort of SiPR-MBNM.

[0115] Fig.21 This is an electron microscope image of SiPR-MBNM and meltblown fibers. From a microscopic perspective, SiPR-MBNM presents a criss-cross ultrafine fiber network structure. The fiber network has a high density of arrangement between fibers, and all long fibers are staggered, bent and folded, with few broken fibers. At the same time, the surface of each fiber is smooth and flat, and the diameter is evenly distributed and controlled within 5μm. The fiber network structure and fiber diameter give SiPR-MBNM the structural characteristics of high porosity and small pore size, which are standard meltblown material structural characteristics. According to the heat transfer mechanism, the structure can effectively reduce the heat transfer path, increase the heat transfer resistance, and reduce thermal convection, which enables SiPR-MBNM to obtain better thermal insulation performance.

[0116] Thermal conductivity is an important indicator to measure the performance of thermal insulation materials. Thermal conductivity can directly show the thermal insulation performance of materials. The lower the thermal conductivity, the weaker the thermal conductivity of the material, which means it has a better thermal insulation effect. Table 1 below shows the thermal conductivity of SiPR-MBNM and mainstream thermal insulation materials. The table shows that SiPR-MBNM has a lower thermal conductivity and a more stable floating range than existing mainstream thermal insulation materials, which is only 0.03-0.037W·m -1 ·K -1 According to the analysis of heat conduction theory, SiPR-MBNM can obtain a lower thermal conductivity mainly due to the melt-blown process. The ultra-fine fibers spun by melt-blown effectively reduce the transfer path of solid-state heat conduction. At the same time, the structural characteristics of high porosity and small pore size effectively control heat convection and heat radiation. The synergistic effect of the two effectively reduces the heat conduction inside SiPR-MBNM, giving it excellent thermal insulation performance.

[0117] Table 1 Thermal conductivity of various materials

[0118]

[0119] In order to more intuitively evaluate the thermal insulation performance of SiPR-MBNM, the present invention directly places SiPR-MBNM on a heating plate for heating, and uses a thermal infrared imaging camera to record the temperature changes on its surface. Fig. 22 The surface temperature of SiPR-MBNM with different thicknesses at different stages during the heating process of the heating plate is shown. When the heating plate temperature is heated to 150°C, the center temperature of the 2mm thick SiPR-MBNM is only 67.8°C, while the center temperature of the 4mm thick SiPR-MBNM is further reduced to 46.4°C. As the temperature of the heating plate continues to increase, the temperature difference (ΔT) between the SiPR-MBNM and the heating plate becomes larger and larger. When the heating plate temperature is heated to 300°C, the center temperature of the 2mm SiPR-MBNM is only 160.4°C, and the ΔT has reached 139.6°C, while the ΔT of the 4mm SiPR-MBNM is as high as 169.4°C.

[0120] The thermal insulation performance of SiPR-MBNM is observed from the side view of the SiPR-MBNM-4mm during the heating process ( Fig.23 ). From the figure, it can be observed that the temperature changes when the heat passes through SiPR-MBNM. As the height from the heating plate increases, the detected temperature decreases significantly. When the contact position with the heating plate is only 1mm, the temperature only drops from 250℃ to 194.6℃, and then drops to 146.4℃ when the height is 2mm. Finally, the temperature is only 102.9℃ when the height is 4mm. This shows that the heat transferred by the heating plate is effectively delayed after passing through the internal structure of SiPR-MBNM, successfully achieving excellent thermal insulation effect.

[0121] like Fig.24 As shown in (a), the thermal insulation effect of SiPR-MBNM is stable during continuous heating on the heating plate, and the heating rate is lower than that of the heating plate. After 3 minutes of continuous high-temperature heating, the center temperature of SiPR-MBNM did not continue to rise, and a high ΔT was maintained between it and the heating plate, still maintaining excellent thermal insulation performance, and ΔT was stably maintained at around 160°C, without performance degradation due to long-term heating. In addition, during the heating and cooling cycle test, SiPR-MBNM ( Fig.24 (b)), the two heating processes show the same temperature rise trend and thermal insulation effect, which indicates the thermal insulation stability of SiPR-MBNM when repeatedly heated in a high temperature environment. It is worth noting that region II is the natural cooling curve of SiPR-MBNM after the heating plate is removed. It takes less than 30 seconds for SiPR-MBNM to drop from 300°C to 50°C during the natural cooling process, which further confirms the excellent thermal insulation performance of SiPR-MBNM and also demonstrates the good heat dissipation ability of the material.

[0122] Flame retardancy is one of the essential properties of thermal insulation materials for personal thermal protection. Compared with some commercial thermal insulation materials for personal thermal protection, SiPR-MBNM exhibits inherent flame retardancy due to the properties of PF after curing. Fig.25 The graph is a graph of the combustion behavior of SiPR-MBNM and commercial thermal insulation materials characterized by microcalorimetry. The results show that SiPR-MBNM only exhibits a low peak heat release rate value after 470°C, with the highest being only 12.06W / g. In contrast, commercial thermal insulation materials have two peaks during the heat release rate test, one of which shows a higher heat release rate value at low temperature, reaching 18.55W / g, and the second heat release rate peak is at 400°C, and the heat release rate value is also higher than SiPR-MBNM at 16.67W / g.

[0123] Fig.26 This is a diagram showing the open flame combustion test of SiPR-MBNM and commercial thermal insulation materials. It can be clearly seen from the figure that no open flame was observed when SiPR-MBNM was burning with the outer flame of the alcohol lamp, and no combustion occurred during the test when it was in contact with or away from the flame ( Fig.26 (a)); in addition, Fig.26 (c) It can be clearly observed that after flame burning, only carbonization of SiPR-MBNM fibers occurred, and the structure of melt-blown materials was still maintained, which played a certain role in thermal insulation. In contrast, the flame retardant properties of commercial thermal insulation materials are not ideal because the flame retardant properties are obtained by post-treatment of the fabric. Fig.26(b) shows that the commercial thermal insulation material produced open flames after contact with the outer flame of the alcohol lamp. At the same time, the commercial thermal insulation material was severely melted and condensed after burning, and the fabric structure was severely damaged and could no longer play a role in thermal insulation protection (26 (d)). Further limiting oxygen index (LOI) test of SiPR-MBNM showed that its LOI value was 34, which has better flame retardant properties than common flame retardant fabrics, flame retardant materials and thermal insulation materials on the market (see Table 2).

[0124] Table 2 Limiting oxygen index of various materials

[0125]

[0126] It is worth noting that due to the inherent combustion characteristics of PF without harmful gas smoke, SiPR-MBNM does not produce harmful, irritating odors and smoke during the combustion process, while commercial insulation materials will release a large amount of toxic gases with irritating odors during the combustion process, and black smoke will also appear, which will cause secondary harm to users during the application process. Therefore, the clean combustion also makes SiPR-MBNM more adaptable in the field of personal protective equipment.

[0127] In summary, SiPR-MBNM has excellent heat insulation and flame retardant properties, and therefore has broad potential application prospects in the field of personal thermal protection equipment. In order to test the application performance and possibility of SiPR-MBNM in personal thermal protection equipment, the present invention has designed and produced a SiPR-MBNM thermal protection glove (STPG), which is composed of four layers of materials with different functions, namely: a flame retardant outer layer, a waterproof layer, a thermal insulation layer and an inner lining. Among them, SiPR-MBNM is used as a thermal insulation layer, and other materials are consistent with the common materials of commercial thermal insulation gloves on the market.

[0128] In order to characterize the actual protective performance that STPG can provide when working in a high-temperature environment, a thermocouple was placed in the STPG to detect the perceived temperature in real time. Then the STPG was worn in direct contact with the fire source to detect the actual feeling of the experimenter wearing it and the temperature change inside the glove. Fig. 27 As shown in (a1), when STPG is exposed to flame for a short time, the flame retardant layer provides effective flame retardancy. At the same time, SiPR-MBNM as a thermal insulation layer also provides good thermal insulation protection. There is no obvious change on the outside of the glove, and the internal temperature is also maintained at a low level. Fig. 27 (b) shows that the internal temperature of STPG did not change significantly during the first few seconds of contact with the flame (STPG began to contact with the flame at 10s), which indicates that STPG has excellent thermal protection ability when exposed to flame burning conditions for a short time, protecting the human body from external high temperature heat. On the other hand, when STPG was in contact with the flame for a long time, the outer flame retardant layer began to smoke and deform and break ( Fig. 27 (a2)). At this time, due to the long-term flame burning, the internal temperature of STPG gradually increased. When the external flame retardant layer was damaged, the internal temperature of the glove reached 41.5°C after long-term high-temperature burning, which is still within the acceptable temperature range for the human body. SiPR-MBNM can still provide effective thermal insulation protection after the flame retardant layer is damaged and in contact with the flame.

[0129] In addition, STPG can be used to protect the human body from burns when contacting or grasping high-temperature objects for a long time. Fig. 27 (c) is an infrared display of grabbing a high-temperature object while wearing STPG. The picture shows that the center temperature of the high-temperature metal block is as high as 160℃ and is in direct contact with STPG. At the same time, the high-temperature heat radiation of the metal block continues to release heat radiation to other uncontacted parts of the glove. The overall temperature of the outer part of the glove is higher than 100℃, but there is no obvious temperature rise or burning sensation inside. The tester can hold the high-temperature metal block for a long time without getting hurt.

[0130] In the present invention, SiPR is melt-spun and melt-blown to prepare SiPRF and SiPR-MBNM, and various performance tests are performed to characterize their performance and application capabilities. The main conclusions are as follows:

[0131] 1) SiPRF was successfully prepared by melt spinning using SiPR. Compared with unmodified PF, it has better spinnability and flexibility, and can be spun at high speed to produce continuous long fibers with fine diameter, high strength and softness. SiPRF-7 exhibits excellent mechanical properties and good heat resistance, with tensile breaking strength and tensile breaking elongation reaching 245.5MPa and 6.63% respectively, and the residual carbon rate increased by 11% to 61% compared with PFF.

[0132] 2) The ultrafine fiber nonwoven material SiPR-MBNM was prepared with SiPR-7 as raw material through melt-blowing process. The thermal insulation and flame retardant test showed that SiPR-MBNM has excellent thermal insulation performance due to its ultrafine fiber porous structure, and the thermal conductivity is only 0.03-0.037W·m-1·K-1. In the 300℃ heating plate environment, the temperature difference (ΔT) between SiPR-MBNM-2mm and the heating plate can reach 139.6℃, and the ΔT of SiPR-MBNM-4mm is as high as 169.4℃; Due to the inherent flame retardant properties of PF, SiPR-MBNM exhibits excellent flame retardant properties, with a maximum heat release rate of only 12.06W / g and an LOI value of 34. In the flame combustion test, there is no melting deformation, only fiber carbonization, and the melt-blown material structure is still maintained. At the same time, no harmful or irritating gas is generated during the combustion process;

[0133] 3) Insulating gloves STPG were made using SiPR-MBNM as the insulating layer. During the open flame burning test, the temperature inside the glove was always kept within the acceptable temperature range for the human body. Even if the outer insulating layer was destroyed and in direct contact with the flame, it still provided effective insulation for the human body. At the same time, wearing STPG allows long-term contact or grasping of high-temperature objects, protecting the human body from burns from high-temperature objects during actual use, confirming that SiPR-MBNM has great application potential in the field of personal thermal protection equipment.

[0134] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a silane-modified high-ortho-phenolic resin, characterized in that: The steps include: S1. Synthesizing a high-ortho-phenolic resin intermediate by ortho-induction of a divalent metal salt catalyst; S11, mixing phenol, formaldehyde and zinc acetate into a reactor, and reacting under heating conditions; S12, the first stage pre-reaction is continued at 75-85°C for 3-5 hours; S13, then adding hydrochloric acid catalyst to adjust the pH value to 1.5-2.5, heating the mixture to reflux temperature and continuing the reaction for 1-3 hours to obtain a high-ortho-phenolic resin intermediate; S2, introducing a siloxane flexible chain through a silane modifier to modify and extend the methylene bond rigid chain of the phenolic resin to obtain a silane-modified high-ortho-phenolic resin; The silane modifier is dimethyldimethoxysilane modifier; the mass ratio of phenol in the dimethyldimethoxysilane modifier is set to 3% to 11%.

2. The method for preparing a silane-modified high-ortho-phenolic resin according to claim 1, wherein: The step of obtaining the silane-modified high-ortho-phenolic resin in S2 comprises the following steps: S21, adding dimethyldimethoxysilane as a modifier, and continuing the reaction for 2-8 hours to obtain a mixture containing a silane-modified high-ortho-phenolic resin; S22, dissolving the mixture in anhydrous ethanol and performing reduced pressure distillation; S23, finally drying in a vacuum oven at 100-150°C for 12-36 hours.

3. A method for preparing silane-modified high-ortho-phenolic fiber, characterized in that: The preparation is carried out using the silane-modified high-ortho-phenolic resin prepared by the preparation method described in claim 1 or 2 as a raw material.

4. The method for preparing a silane-modified high-ortho-phenolic fiber according to claim 3, characterized in that: The preparation method comprises the following steps: A1. Before melt spinning, place the silane-modified high-ortho-phenolic resin in a vacuum oven at 80-120°C and dry for 2-8 hours; A2, spinning is completed by a melt spinning machine; A3, soaking the melt-spun fiber in a cross-linking bath containing 10-25% hydrochloric acid and 10-25% formaldehyde for curing, heating from 25°C to boiling point at a heating rate of 5-35°C / h and maintaining heating for 1-3 hours; A4. Wash the cured fiber with deionized water for two to three times, and heat treat it at 120-250° C. for 1-3 hours to obtain silane-modified high-ortho-phenolic fiber.

5. A method for preparing a silane-modified high-ortho-phenolic melt-blown nonwoven material, characterized in that: The preparation is carried out using the silane-modified high-ortho-phenolic resin prepared by the preparation method described in claim 1 or 2 as a raw material.

6. The method for preparing a silane-modified high-ortho-phenolic melt-blown nonwoven material according to claim 5, characterized in that: The preparation method comprises the following steps: B1. Dry the silane-modified high-ortho-phenolic resin in a vacuum oven at 80-120°C for 2-8 hours; B2. Prepare melt-blown nonwoven material by melt-blown machine, and the processing temperature of melt-blown and hot air drawing temperature are controlled at 100-150°C; B3, the obtained melt-blown nonwoven material is immersed in a cross-linking bath containing 10-25% hydrochloric acid and 10-25% formaldehyde for curing, and heated from 25°C to boiling point at a heating rate of 5-35°C / h and kept heated for 1-3 hours; B4. Wash the cured fibers two to three times with deionized water, and heat treat the fibers at 120-250° C. for 1-3 hours to obtain a phenolic melt-blown nonwoven material.

Citation Information

Patent Citations

  • Preparation method of epoxy chloropropane toughened high-ortho phenolic fiber

    CN103469342A

  • Organic silicon modified phenolic resin and preparation method thereof

    CN106496473A